Violence, Aggression and Insecurity in the Niger Delta of Nigeria: An Exploratory Study of the Militancy in the Region - Enyidah-OkeyOrdu, Gilbert (Advances in Social Sciences Research Journal, 2017)
The Niger Delta region is endowed with oil and natural gas, and contributes enormously to the building of Nigerian economy. With the Niger Delta’s economic contributions, Nigeria rewarded the people in the region with environmental pollution, abject poverty and unemployment. While the oil companies exploited and marginalized the Niger Delta region, the militants emerged with violence and aggression to disrupt oil production, installations and allied facilities in an effort to compel the federal government and oil companies to meet their demands for human capacity building and general infrastructural developments as well as compensations for the widespread exploitations and environmental pollutions that are going on in this region. The failures of the oil companies and the federal government of Nigeria to comply with the demands of the militants fueled violence, aggression and insecurity in the region. This study use secondary data to examine the critical nature of the Niger Delta militants’ violence and aggression in Nigeria and its effects on the country’s national economy. This paper concludes that the federal government of Nigeria, with the support of the oil companies, should genuinely address the demands of the Niger Delta people and strictly adhere to international environmental standards as regards land and water preservation.